Karakteristik Pelaku Kejahatan Transnasional Terorganisasi di Indonesia dan Eropa - Naseh, Muhammad; Ikhwanuddin, Ikhwanuddin; Ramadhani, Faizal; Kusprabandaru, Agung; Bathara, Beny (Universitas Muhammadiyah Yogyakarta, 2019)
The revolution in information, communication, and transportation technology have connected many different parts of the world and make the distance nearly gone. This immense development is in parallel with the changing of transnational crime. This article offers a comparative study of organized-transnational crime in Indonesia and Europe, especially in the issues of human trafficking, money laundering, drugs smuggling, and terrorism. Based on the method from Klaus von Lampe, this article aims to see the similarities and differences between both countries by the characteristic and intensity of the crime. This article identifies the challenge related to logistic as a key to overcoming any infringement in the border area. Another finding is the transnational crime in both countries has similarities in modes of operation. In which most of the criminal activity in both countries take advantage of the weakness of geographic and demographic condition, and security faint. The actors are seeking situations which give the advantages of whether in economics or the opportunity to commit the criminal act itself.